2010
DOI: 10.1111/j.1365-2249.2010.04281.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of both circulating CD4+CD25+CD127low/neg and CD4+CD8neg invariant natural killer regulatory T cells in stable heart transplant recipients

Abstract: SummaryA cross-regulation between two regulatory T cell (Treg) subsets [CD4 + CD25 + and invariant natural killer (NK) T -iNK T] has been described to be important for allograft tolerance induction. However, few studies have evaluated these cellular subsets in stable recipients as correlates of favourable clinical outcome after heart transplantation. Treg and iNK T cell levels were assayed by flow cytometry in peripheral blood samples from 44 heart transplant recipients at a 2-year interval in 38 patients, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…Notably, a low CD4þ/CD8þ ratio is also generally considered as a predictor for the severity of disease or a poor prognosis. 16,17 Accordingly, our results indicated that less trauma and effects on immune function resulting from laparoscopic surgery might be good for recovery postoperatively and have potential benefits on long-term survival.…”
Section: Discussionmentioning
confidence: 66%
“…Notably, a low CD4þ/CD8þ ratio is also generally considered as a predictor for the severity of disease or a poor prognosis. 16,17 Accordingly, our results indicated that less trauma and effects on immune function resulting from laparoscopic surgery might be good for recovery postoperatively and have potential benefits on long-term survival.…”
Section: Discussionmentioning
confidence: 66%
“…, 26,27 showing reduced numbers of circulating CD4 + CD25 high Foxp3 + regulatory T cells in chronically rejecting patients compared with patients with stable graft function. Reduced percentages of circulating CD25 + CD127 low CD4 + T cells were also found in stable heart transplant recipients at 2 years after transplantation 28 . This might reflect a sequestration of these cells in the allograft.…”
Section: Discussionmentioning
confidence: 83%
“…Reduced percentages of circulating CD25 + CD127 low CD4 + T cells were also found in stable heart transplant recipients at 2 years after transplantation. 28 This might reflect a sequestration of these cells in the allograft. Indeed, in a murine kidney allograft model, a higher and sustained level of Foxp3 + regulatory T cells has been demonstrated in tolerated compared with rejecting allografts.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + /CD8 can reflect the immune balance of an organism, if the ratio is low, it means that body immune function is decreasing and may increase tumor proliferation. Of note, a low ratio is commonly regarded as the index for severe disease or a poor prognosis (21)(22)(23). In the present study, CD3 + , CD4…”
Section: Discussionmentioning
confidence: 81%